Analysis of Factors Influencing Taxpayer Compliance in Paying Regional Taxes in Mataram City - Saumatur Rizky; Hailuddin Hailuddin; Sujadi Sujadi (Indonesian Development Economics and Localities, 2026)
This study aims to analyze the influence of the tax administration system, tax services, tax rates, tax audits, tax law enforcement, and tax knowledge on taxpayer compliance in paying local taxes in Mataram City. This study uses a quantitative approach with an associative research type. Data were collected through distributing questionnaires to 100 taxpayer respondents in Mataram City and analyzed using multiple linear regression with the help of SPSS software. The results of the study indicate that simultaneously, all independent variables have a significant effect on taxpayer compliance. Partially, the variables of tax services, tax rates, tax audits, and tax law enforcement have a significant influence, while the tax administration system and tax knowledge have no significant effect. Tax law enforcement is the most dominant factor in influencing taxpayer compliance. In connection with these findings, it is recommended that the Mataram City Government improve and strengthen aspects of tax law enforcement firmly and consistently. The application of administrative and criminal sanctions for violations of tax obligations must be carried out effectively to create a deterrent effect for non-compliant taxpayers.